2001
DOI: 10.1161/01.hyp.37.2.623
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic Acid Mediates Angiotensin II–Induced Phospholipase D Activation in Vascular Smooth Muscle Cells

Abstract: Abstract-Angiotensin II (Ang II) activates cytosolic phospholipase A 2 (cPLA 2 ) and phospholipase D (PLD) in rabbit vascular smooth muscle cells (VSMCs). Ang II also activates ras/mitogen-activated protein (MAP) kinase in VSMCs; this activation is mediated by 20-hydroxyeicosatetraenoic acid (HETE) and 12(S)-HETE, which are metabolites of arachidonic acid generated by cytochrome P450 4A and lipoxygenase, respectively, produced on activation of cPLA 2 . The purpose of this study was to determine if Ang II-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…In cultured vascular smooth muscle cells from adult rabbits (19) and rats (33) as well as in isolated renal arterioles (31), 20-HETE induces the phosphorylation of ERK1/2, a MAPK that plays a pivotal role in the proliferation induced by the activation of receptor tyrosine kinases and G proteincoupled receptors (9). Blockade of the formation of 20-HETE attenuated norepinephrine-induced and ANG II-induced ERK1/2 phosphorylation, suggesting that 20-HETE may serve as a second messenger of these growth factors (20,24). The same investigators also showed that 20-HETE contributed to ANG II-induced neointimal thickening in the injured carotid artery (43).…”
Section: Discussionmentioning
confidence: 99%
“…In cultured vascular smooth muscle cells from adult rabbits (19) and rats (33) as well as in isolated renal arterioles (31), 20-HETE induces the phosphorylation of ERK1/2, a MAPK that plays a pivotal role in the proliferation induced by the activation of receptor tyrosine kinases and G proteincoupled receptors (9). Blockade of the formation of 20-HETE attenuated norepinephrine-induced and ANG II-induced ERK1/2 phosphorylation, suggesting that 20-HETE may serve as a second messenger of these growth factors (20,24). The same investigators also showed that 20-HETE contributed to ANG II-induced neointimal thickening in the injured carotid artery (43).…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins have been involved in mediating PLD activation elicited by ANG II in VSMC such as heterotrimeric and small G proteins (1, 38) and phospholipase A 2 (27). PLD may contribute to the functional effects of ANG II on VSMC through the formation of phosphatidic acid and/or its metabolites (27)(28)(29)(30). ANG II selectively activates PLD2 isoform in VSMC (27).…”
mentioning
confidence: 99%
“…PLD may contribute to the functional effects of ANG II on VSMC through the formation of phosphatidic acid and/or its metabolites (30). Several proteins have been involved in mediating PLD activation elicited by ANG II in VSMC such as heterotrimeric and small G proteins (1,38) and phospholipase A 2 (27). PLD may contribute to the functional effects of ANG II on VSMC through the formation of phosphatidic acid and/or its metabolites (27)(28)(29)(30).…”
mentioning
confidence: 99%
See 2 more Smart Citations